KOMPATIBILITAS BEBERAPA SPESIES Bacillus SEBAGAI BIOAKTIVATOR PUPUK ORGANIK HAYATI - Yun Sondang; Muflihayati Muflihayati; Khazy Anty; Ramond Siregar (Jurnal Agroteknologi, 2023)
Bacteria is a potential agent in biological organic fertilizer”s process. The rate of decomposition of organic matter in biological organic fertilizers process depends on the role of funtional bacteria, the type of organic matter and the microenvironment.  Bacteria that are inoculated into biological organic fertilizer’s matter must be synergistic among them, so that their role as as bioactivators more efficient.  A compatibility experiment among the bacteria isolates used as bioactivators have to be done in order to  obtain an effective and efficient biological organic fertilizer. The objevctive of the research is to obtain information on the compatible nature of the bacterial isolates. The research was conducted at the Plant Protection Laboratory of the Payakumbuh State Agricultural Polytechnic, West Sumatra from July to August 2022. The research method began with the rejuvenation bacterial isolates of Bacillus cereus, Bacillus subtilis, Bacillus thuringiensis on NA media, then continued with a compatibility experiment  using the dual culture method on NA and King’s B medium, so there were a total of 12 treatments (single and combination) with three replications. The results of the compatibility experiment on the three Bacillus bacteria did not form a halo inhibition zone and were compatible with the compatibility index value (IK) 0.67-1 on NA medium and 0.90-1.00 on King’s B medium, meaning that the growth between the three Bacillus bacteria did not inhibit each other, so that all Bacillus bacteria could be used as a bioactivator simultaneously in biological organic fertilizer’s process.